Participation of the autonomic cardiac system in dogs with chronic myxomatous degeneration of the mitral valve - Navarrete, R. A. [UNESP]; Camacho, A. A. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
An exploratory multivariate analysis of factors of echocardiographic variables and those of the Holter test of 38 dogs with MVMD staged in three classes (class 1a, class 1b, class 2) of congestive heart failure proposed by the ISACHC. The purpose of this analysis was learning the processes that would explain the behavior of the variables described, using exploratory multivariate techniques of factors. Five independent factors were determined (PNS to SF) which altogether explain 82.17% of the shared variance of the data. It was identified that among the five factors, the first process (PNS) is the first factor in importance, recruiting the highest percentage of variance (37.96%) and represents the participation of the cardiac autonomic nervous system.
Keywords: endocardiosis; heart rate variability; factors; cardiac autonomic nervous system